Recent advances in fermentative production of C4 diols and their chemo-catalytic upgrading to high-value chemicals - Varma, Abhishek R.; Shrirame, Bhushan S.; Maity, Sunil K.; Agrawal, Deepti; Malys, Naglis; Rios-Solis, Leonardo; Kumar, Gopalakrishnan; Kumar, Vinod (Elsevier, 2023)
The current era is witnessing the transition from a fossil-dominated economy towards sustainable and low-carbon green manufacturing technologies at economical prices with reduced energy usage. The biological production of chemical building blocks from biomass using cell factories is a potential alternative to fossil-based synthesis. However, microbes have their own limitations in generating the whole spectrum of petrochemical products. Therefore, there is a growing interest in an integrated/hybrid approach where products containing active functional groups obtained by biological upgrading of biomass are converted via chemo-catalytic routes. The present review focuses on the biological production of three important structural isomers of C4 diols, 2,3-, 1,3-, and 1,4-butanediol, which are currently manufactured by petrochemical route to meet the soaring global market demand. The review starts with justifications for the integrated approach and summarizes the current status of the biological production of these diols, including the substrates, microorganisms, fermentation technology and metabolic/pathway engineering. This is followed by a comprehensive review of recent advances in catalytic upgrading of C4 diols to generate a range of products. The roles of various active sites in the catalyst on catalytic activity, product selectivity, and catalyst stability are discussed. The review also covers examples of integrated approaches, addresses challenges associated with developing end-to-end processes for bio-based production of C4 diols, and underlines existing limitations for their upgrading via direct catalytic conversion. Finally, the concluding remarks and prospects emphasise the need for an integrated biocatalytic and chemo-catalytic approach to broaden the spectrum of products from biomass.
Keywords: Butanediols; Fermentation; Metabolic engineering; Heterogeneous catalysis; 1,3-Butadiene; 3-Buten-1-ol; 3-Buten-2-ol; Methyl ethyl ketone